Aerodynamic vocal measurements from professional singers (Research, Society and Development, 2020)
The objective of the work was to characterize the aerodynamic vocal measurements of professional singers according to gender and the reference values. This is a cross-sectional, quantitative and retrospective study with 23 professional singers between 19 and 55 years old. The maximum phonation times of /a/, /i/, /u/, /s/, /z/, /e/, /ė/; sound pressure levels; and s/z and ė/e ratios were analyzed. The data were analyzed statistically. Men showed maximum phonation time of /e/, /i/ and /u/ significantly below the reference values and women showed significantly lower values of the maximum phonation time of /e/, and maximum phonation time of /i/ e /u/ significantly within the expected. The usual sound pressure level and maximum sound pressure level were significantly higher than the reference values in both genders. It was concluded that, in the group of professional singers analyzed, the results of the maximum phonation time suggest greater incoordination in the respiratory and laringeal control of the prolonged emission in men. The results of sound pressure level suggest greater vocal effort in the emission for both genders, or adjustments due to the muscular training inherent to the profession.